Respiratory support of patients with pneumonia in the context of the COVID-19 pandemic - M. Mirsaliyev; K. Kashikova; A. Zholdybayeva (Medičnì Perspektivi)
The purpose of this study is to evaluate and analyse existing methods of supporting individuals suffering from pneumonia due to the coronavirus infection, as well as to find new ones. The following methods were used in a randomised controlled trial: artificial lung ventilation (ALV), non-invasive ventilation, oxygen therapy using oxygen masks and nasal cannulas, penetrating ventilation with high oxygen flow, high-flow nasal oxygen therapy; advantages and disadvantages of such methods. The analysis of a sample of 200 patients aged 18-80 years, among whom there were both women and men with different levels of severity of the disease, was carried out. The study showed that the use of penetrating ventilation with high oxygen flow significantly improves blood oxygenation and reduces the requirement for lung intubation and ALV. However, minimally invasive respiratory support and oxygen treatment have also proven to be effective methods of respiratory support. When using non-invasive ventilation and penetrating ventilation with high oxygen flow, higher survival rates and shorter hospital stay were observed in patients with pneumonia caused by coronavirus infection, compared with the use of ALV. The study revealed that the use of artificial respiration may result in more severe adverse effects, such as lung barotrauma, so it is recommended to use it only in the absence of other effective methods of respiratory support. Thus, the results of the study emphasise the need for an individual approach when choosing a method of respiratory support in patients with pneumonia caused by coronavirus infection, and also confirm the effectiveness of minimally invasive respiratory aid and high-flow oxygen penetrating ventilation in the treatment of this pathology.